Metafounders are related to Fst fixation indices and reduce bias in single - step genomic evaluations - García Baccino, Carolina Andrea (2017)
Fil: García Baccino, Carolina Andrea. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Animal. Buenos Aires, Argentina.